PENERAPAN MONOPOLI DAN KARTU BACA UNTUK LITERASI DAN WAWASAN ANAK PEKERJA MIGRAN INDONESIA (PMI) DI MALAYSIA - Aqila, Syarla; Sumarlan, Daffa; Nuha, Afina Sabrina Naila; Qanitha, Hana; Abas, Fathina Narindra; Namida, Aisha Nura; Putry, Sindy Tarisma; Ramadhan, Sultan Rizqhi; Firdaus, Arifah Salwa; Musthafa, Hilman; Azizah, Siti Nur (CV. Alina, 2024)
The MONOKACA (Monopoli Nusantara Cerdas Anak) program was initiated to address the lack of formal education access for Indonesian children residing in Malaysia, particularly children of Indonesian migrant workers. This program aims to enhance basic literacy skills and instil national values through interactive educational games. The program includes two sessions: LAPAR (Fun Literacy through Card Games), which focuses on reading, writing, and arithmetic, and MOPULAU (Monopoli Pulau and Rupiah), which introduces Indonesian history and culture. Evaluation results indicate that the MONOKACA program improved basic literacy, national awareness, and social skills such as teamwork and communication among these children. With its engaging and interactive approach, this program is expected to have a long-term impact on preserving the national identity among Indonesian children in Malaysia.